189k views
1 vote
Please please help!!!!!!!!

Please please help!!!!!!!!-example-1
User Hohohodown
by
5.4k points

2 Answers

4 votes
I think the answer is a
User CCKx
by
5.4k points
5 votes

Answer:

C

Explanation:

To find the inverse, let y = f(x) then rearrange making x the subject, that is

y = 5(x + 3)³ - 2 ( add 2 to both sides )

y + 2 = 5(x + 3)³ ( divide both sides by 5 )

(x + 3)³ =
(y+2)/(5)

Take the cube root of both sides

x + 3 =
\sqrt[3]{(y+2)/(5) }

Subtract 3 from both sides

x =
\sqrt[3]{(y+2)/(5) } - 3

Change y back into terms of x, so


f^(-1) (x ) =
\sqrt[3]{(x+2)/(5) } - 3 → C

User Artur INTECH
by
5.2k points